Innovation in regulated electricity distribution networks: A review of the effectiveness of Great Britain's Low Carbon Networks Fund. (July 2018) - Frame, Damien; Hannon, Matthew; Bell, Keith; McArthur, Stephen
Abstract: Introduced in 2010, the Low Carbon Networks Fund (LCNF) was a major development in the regulatory regime for electricity distribution networks in Great Britain, yet evaluation of its design and implementation has been limited. This paper examines the type and quality of innovation arising from the LCNF. Novel frameworks for assessing innovation project activity and learning are presented and results from their application to the LCNF are discussed. Reduction of uncertainty through the production of high quality evidence is argued to be the primary purpose of innovation project funding support. The analysis of LCNF project activity finds a step change in Research Development & Demonstration (RD&D) spend and stakeholder engagement by network licensees in Britain; however, the innovation observed was considered to be conservative and incremental in nature. It was found that the LCNF lacked a strategic approach to targeted learning and the reduction of uncertainty for innovation priority areas. Project learning outputs were contradictory and inconclusive for several innovations. Strategic learning should be a core part of policy makers' design of innovation funding mechanisms for energy technology, and a framework for shaping, capturing and assessing the learning outputs of funded innovation projects is essential. Highlights: Recent innovation activity in GB electricity distribution networks is examined. A step-change in innovation spend has occurred. Innovation activity has been conservative and incremental. Project learning outputs have been inconclusive for several innovations. A strategic approach to learning is crucial for innovation funding mechanisms.